Mobile systems for assessing air quality: available solutions and application examples - Zboralski, Dominik; Kunz, Mieczysław (Bulletin of Geography. Physical Geography Series, 2024)
Air quality is of interest to many institutions and individuals, including, above all, the informed residents of monitored areas. The state of the air and its pollution level are very important to the health, life and functioning of any community living in urban areas. A poor state of the environment has inevitable health consequences; in the case of the air, these are mainly respiratory or cardiovascular diseases. This element intensifies during the heating season when compounds from the combustion of banned substances and materials are emitted into the atmosphere. The quality of the lowest layer of the atmosphere can be studied using various recording systems and detectors. These include continuous monitoring of the state of the air by spatially dispersed stationary measuring stations operating in the State Environmental Monitoring system. Their location is usually associated with significant traffic intensity in their immediate vicinity rather than high local residential density. The measurement network is also co-created and densified by alternative point air-quality-monitoring systems proposed by private companies or community organizations (e.g., Airly, Sensor.Community, LoVo). A precious source of reliable local air quality data is mobile recording systems, which use unmanned aircraft or vehicles – objects in motion – and carry out periodic inspections, control missions or measurements. Examples of such solutions in the Polish market are Sniffer4D, Nosacz II and AirDrone. This paper aims to analyze and compare the available mobile measurement systems in terms of technical and usability for air quality research, along with a description of example areas where they are being used and implemented in practice. In addition, selected results of tests carried out with the Sniffer4D system at three testing grounds in Toruń are presented as part of a measurement campaign using an unmanned aerial vehicle and a passenger car.